Lipopolysaccharide (LPS) from E. coli has detrimental effects on the intestinal morphology of weaned pigs (2011)
ABSTRACT: Early weaning predisposes the pig intestine to structural and functional alterations, due to the increase in E. coli populations. These bacteria use the lipopolysaccharide (LPS) derived from their cell wall as an important pathogenic factor. Little is known about the effects of LPS on the intestinal morphology. Such knowledge could be helpful in understanding the pathogenesis of post-weaning enteritis, which is needed to design therapeutic strategies. Objective: this study aimed to evaluate the effects of the oral intake of LPS on the morphology of intestinal villi and glands of weaned pigs. Methods: the study used 52 pigs weaned at 21 days. The animals were fed a basal diet added with four levels of LPS (0.0, 0.3, 0.5 and 1.0 μg/mg of food) for 10 days. Pigs were sequentially slaughtered on days 1, 5, 7 and 10 after weaning, and samples of small intestine were taken to evaluate morphological parameters by computerized image analysis. The statistical design used was randomized blocks in a 4x4 factorial arrangement. Results: results showed that LPS decreases the height and area of intestinal villi, and increases the width of the villi and the depth and width of the intestinal glands. These effects probably contribute to a decreased intestinal nutrient absorption and increase co-infection with other pathogens, thus leading to the post-weaning diarrhea syndrome. Conclusions: this study stresses the usefulness of computerized morphometric analysis to evaluate the effect of LPS on intestinal morphology, so it may be used in future studies to investigate the pathophysiology of the causative agents of enteritis and to evaluate therapeutic strategies.